WHY NS AND BH MASS DISTRIBUTION IS BIMODAL? - Prokhorov, M. E.; Postnov, K. A. (Одеські астрономічні публікації, 2017)
The observed mass distribution for the compact remnants of massive stars (neutron stars and black holes) and its relationship to possible mechanisms for the ejection of the envelopes of type II and Ib/c supernovae is analyzed. The conclusion is drawn that this distribution can be obtained only by a magneto-rotational mechanism for the supernovae with sufficiently long time of the field amplification, and a soft equation of state for neutron stars with limiting masses ∼1.5 - 1.6 M ⊙. Some consequences of this hypothesis are discussed.